Utility of p63 immunohistochemical stain in differentiating urothelial carcinomas from adenocarcinomas of prostate - Nasir Ud Din (Indian Journal of Pathology and Microbiology, 2011)
Background: Prostatic adenocarcinoma and urothelial carcinoma of the urinary bladder are common cancers in men. High grade forms of these tumors may present ambiguous morphologic features that do not permit a definite diagnosis. This distinction between the two tumors has significant staging and therapeutic implications. Hence, an accurate diagnosis is essential for optimal patient care. p63 is a new marker which can be used in this context. It is expressed in most of the urothelial carcinomas and negative in majority of prostatic adenocarcinomas. Aim: To compare the expression of p63 in urothelial carcinomas and adenocarcinomas of prostate. Materials and Methods: Comparative cross--sectional study was carried out at a tertiary cancer hospital from 15 June 2006 to 15 December 2006. Immunohistochemical stain p63 was performed on 50 cases of urothelial carcinoma and 50 prostatic adenocarcinomas. Patients′ name, age, histology numbers, grade of tumor, and expression of p63 were recorded. p63 expression was seen in 44 of 50 urothelial carcinomas (88%). None of the prostatic adenocarcinomas expressed p63. The ages of patients with prostatic adenocarcinoma ranged from 49 to 86 years with a median age of 71 years and 41 to 83 years for urothelial carcinomas with a median age of 60.5 years. Conclusion: p63 can be used as a reliable marker to distinguish prostatic adenocarcinomas from urothelial carcinomas in difficult cases in conjunction with other markers like PSA.